Income distribution in a monetary economy: A Ricardo-Keynes synthesis - Nazim Kadri Ekinci (Levy Economics Institute of Bard College, 2011)
The paper provides a novel theory of income distribution and achieves an integration of monetary and value theories along Ricardian lines, extended to a monetary production economy as understood by Keynes. In a monetary economy, capital is a fund that must be maintained. This idea is captured in the circuit of capital as first defined by Marx. We introduce the circuit of fixed capital; this circuit is closed when the present value of prospective returns from employing it is equal to its supply price. In a steady-growth equilibrium with nominal wages and interest rates given, the equation that closes the circuit of fixed capital can be solved for prices, implying a definitive income distribution. Accordingly, the imputation for fixed capital costs is equivalent to that of a money contract of equal length, which is the payment per period that will repay the cost of the fixed asset, together with interest. It follows that if capital assets remain in use for a period longer than is required to amortize them, their earnings beyond that period have an element of pure rent.
Keywords: D33; D46; E11; E12; E25; 330; income distribution; circuits of capital; monetary economy